2014
DOI: 10.7314/apjcp.2014.15.8.3443
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Neutropenia after Docetaxel-Based Systemic Chemotherapy in Korean Patients with Castration-Resistant Prostate Cancer

Abstract: The aim of this study was to determine predictive factors for neutropenia after docetaxel-based systemic chemotherapy in patients with castration-resistant prostate cancer (CRPC). The study included 40 Korean CRPC patients who were treated with several cycles of docetaxel plus prednisolone from May 2005 to May 2012. Patients were evaluated for neutropenia risk factors and for the incidence of neutropenia. In this study, nine out of forty patients (22.5%) developed neutropenia during the first cycle of docetaxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…Besides 6‐TGN levels, also excessively elevated 6‐MMPR levels have been associated with leucopenia . The increased risk for leucopenia with a lower baseline WBC count has also been reported in the setting of ganciclovir‐ and chemotherapy‐induced leucopenia . In contrast to a previous study, we did not find a correlation between concomitant 5‐ASA use and myelosuppression .…”
Section: Discussioncontrasting
confidence: 77%
“…Besides 6‐TGN levels, also excessively elevated 6‐MMPR levels have been associated with leucopenia . The increased risk for leucopenia with a lower baseline WBC count has also been reported in the setting of ganciclovir‐ and chemotherapy‐induced leucopenia . In contrast to a previous study, we did not find a correlation between concomitant 5‐ASA use and myelosuppression .…”
Section: Discussioncontrasting
confidence: 77%
“…25 DTX usually cause hemotoxicity such as temporary drop in the number of white blood cells and neutropenia. 26 Thus, hematologic toxicity was evaluated in the study. There was no pronounced difference in the counts of red blood cells (RBC), white blood cells (WBC), hemoglobin (HGB), platelets (PLT), lymphocyte (LYM), and neutrophil granulocyte (GRN) tests after treatment (Figure 4E) among At-Lp/siRNA/DTX and other groups, indicating the dual peptides-modified combination delivery system was relatively safe at the test dose.…”
Section: Resultsmentioning
confidence: 99%
“…One of Mfsd2a-based strategies would destroy the BBB and enhance the uptake of drugs temporarily, thus potentially resulting some unexpected damage . DTX usually cause hemotoxicity such as temporary drop in the number of white blood cells and neutropenia . Thus, hematologic toxicity was evaluated in the study.…”
Section: Resultsmentioning
confidence: 99%
“…The rates of FN in these studies were 12.5% for patients with mHSPC who received docetaxel plus hormonal therapy, 7 and 14.0% for mCRPC patients treated with docetaxel‐based chemotherapy 8 . Similarly, a recent real‐world study in Korea reported an FN rate of 22.5% during the first cycle of docetaxel in mCRPC patients 9 …”
Section: Introductionmentioning
confidence: 84%